Aplikasi Teori Self-Care Deficit Orem dalam Konteks Tuna Wisma (Studi Literatur) (The Application of Orem’s Self Care Deficit in Homeless Setting) - Andriany, Megah (Nurse Media Journal of Nursing, 2007)
Homeless health is government and NGO’s responsibilities for creating optimal citizen health status. Homeless is one of community health nursing clients. The Self Care Theory is used in nursing science for giving conceptual framework as a practical guidance and building self care knowledge through research. Orem described self care as a continuing intervention. It was needed and done by adult to be survived, healthy, and wellness. This theory is also used in homeless setting by many experts. This article aims to describe Orem’s Self Care Theory, describe homeless’ self care, and apply Orem’s Self Care Theory in homeless setting.